A Population-Based Examination of Criterion-Level Disparities in the Diagnosis of Borderline Personality Disorder Among Sexual Minority Adults. (June 2021) - Rodriguez-Seijas, Craig; Morgan, Theresa A.; Zimmerman, Mark
Sexual minority individuals are diagnosed with borderline personality disorder (BPD) at higher proportions than heterosexual individuals regardless of presenting psychopathology. It is unclear if such bias is reflective of diagnostician idiosyncrasies or population-based diagnostic/criterion bias. Data from the National Epidemiologic Survey on Alcohol and Related Conditions–III were utilized to examine if differences in BPD endorsement were related to/independent of transdiagnostic factor differences between sexual minority and heterosexual individuals. BPD diagnosis/criterion endorsement was higher among sexual minority compared with heterosexual individuals (odds ratios = 1.47-3.82). Furthermore, when dysfunction/impairment associated with criterion endorsement was ignored, endorsement disparities were magnified. Diagnostic/criterion differences were mostly explained by transdiagnostic factor differences associated with sexual minority status, with some notable exceptions. These results suggest that the predilection toward BPD diagnosis among sexual minority individuals does not appear reflective of criterion-related bias. They further highlight the importance of understanding group-specific forms of psychiatric malaise and reinforce the importance of cultural humility for equitable assessment. These results further raise questions pertaining to the conceptualization and epistemology of BPD as it relates to sexual minority individuals.